EDUKASI MEDIA VIDEO TERHADAP PENINGKATAN CAKUPAN PEMERIKSAAN IVA PADA WANITA USIA SUBUR DI PUSKESMAS RUKUN LIMA - Sisilia Leny Cahyani; Yuliana Dafroyati; Santysima Trinitas Dhajo; Mauritius Timba; Agnes E.S. Pota; Emerensiana Mbeo; Maya E. Sumbi; Maria Seravina K. Bara; Sesilia Perada Laga; Katarina Kemba; Yeni Mariana Tiwe; Rumsiah Ahmad; Emiliana Lori; Maria Bernadina Dupa; Arkadius Dominggu; Marianti A. Gudipun; Katarina N. Timang Riu; Yoseph Rande; Yohanes Sako; Nona Arfa; Wilhelmina Mbejo (Jurnal Cakrawala Ilmiah, 2026)
Background: Cervical cancer is one of the leading causes of death among women in Indonesia. Early detection through Visual Inspection with Acetic Acid (VIA) screening is effective in reducing morbidity and mortality rates, but screening coverage remains low due to a lack of knowledge and motivation among women of childbearing age (WCA). Objective: To analyze the effect of video-based education on improving knowledge, motivation, and IVA screening coverage among WUS at the Rukun Lima Community Health Center. Method: This study is a community nursing service innovation project with a pre-experimental design using a pretest–posttest approach. There were 25 WUS subjects in this study. The intervention was health education using 5–7 minute videos. Measurements were taken using knowledge questionnaires and records of the number of IVA examinations. Results: The average knowledge of WUS increased from 60% to 88%. A total of 84% of respondents stated that they were motivated to undergo IVA examinations. The number of IVA examination visits increased by 85% after the intervention. Conclusion: Education using video media effectively increases knowledge, motivation, and coverage of IVA screening among WUS. Video media can be used as an innovation in health promotion in primary health care.